2019
DOI: 10.3889/oamjms.2019.060
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adding Oral Simvastatin to Topical Therapy for Treatment of Psoriasis: The Vietnamese Experience

Abstract: BACKGROUND:Psoriasis, the prevalence of which ranges from 2% to 3% of the general population, has been recently recognised as not only a chronic inflammatory skin disorder but also an immunometabolic systemic disease. Dyslipidemia is one of the most important comorbidities of psoriasis. Statins, frequently used as anti-hyperlipidemic agents, may be beneficial in the treatment of several autoimmune diseases, including psoriasis, due to their anti-inflammatory and immunomodulatory characteristics. Hence, we hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 23 publications
(24 reference statements)
0
23
0
2
Order By: Relevance
“…In the study by Naseri et al [11], patients from the statin and placebo arms differed substantially in their baseline PASI values (9.51 vs. 5.64, respectively), which may explain the greater improvement in the statin arm. Patients who received either statins or comparators had a similar psoriasis severity in the studies by Trong et al (about 12) and Chua et al (about 6) [26,27].…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In the study by Naseri et al [11], patients from the statin and placebo arms differed substantially in their baseline PASI values (9.51 vs. 5.64, respectively), which may explain the greater improvement in the statin arm. Patients who received either statins or comparators had a similar psoriasis severity in the studies by Trong et al (about 12) and Chua et al (about 6) [26,27].…”
Section: Discussionmentioning
confidence: 63%
“…[11], Trong et al [27], and Vasiuk et al [12]. After exclusion of either study, the effect of statin therapy on PASI values was no longer significant (Table II).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The positive effect of such a commonly administered drug as simvastatin has been widely documented to date in psoriatics. Recently, Trong et al has demonstrated that adding oral simvastatin to antipsoriatic therapy might be beneficial in controlling hyperlipidemia and decreasing the severity of the disease [25]. Going further, an improvement in psoriatic lesions has been observed in diabetic patients treated orally with troglitazone and pioglitazone which are PPAR-g agonists [26,27].…”
Section: Discussionmentioning
confidence: 99%